2014
DOI: 10.1016/j.jpubeco.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Letting the briber go free: An experiment on mitigating harassment bribes

Abstract: This paper examines the effectiveness of using asymmetric liability to combat harassment bribes. Asymmetric liability is a mechanism where bribe-takers are culpable but bribe-givers have legal immunity. Results from our experiment indicate that while this policy has the potential to significantly reduce corrupt practices, weak economic incentives for the bribe-giver, or retaliation by bribetakers can mitigate the disciplining effect of such an implementation. Asymmetric liability on its own may hence face chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 22 publications
1
115
0
3
Order By: Relevance
“…Das-Gupta (2007) categorizes bribes into 2 groups as coercive bribes and voluntary bribes but both are pernicious for people hence subsequently he argues that people in India have multi-fold suffered because of such bribes. Besides Quah"s (2008) note on voluntary bribes as an unethical as well as an equally serious problem for society, Abbink et al (2014), using a lab experiment among students, found that all sorts of corruptions as serious problem in development of India.…”
Section: Sordid South-asian Situation [Discussion Of Real Situation]mentioning
confidence: 99%
“…Das-Gupta (2007) categorizes bribes into 2 groups as coercive bribes and voluntary bribes but both are pernicious for people hence subsequently he argues that people in India have multi-fold suffered because of such bribes. Besides Quah"s (2008) note on voluntary bribes as an unethical as well as an equally serious problem for society, Abbink et al (2014), using a lab experiment among students, found that all sorts of corruptions as serious problem in development of India.…”
Section: Sordid South-asian Situation [Discussion Of Real Situation]mentioning
confidence: 99%
“…17 For a general discussion, see Leslie (2004). There is also some recent experimental evidence; for example, Abbink et al (2012).…”
Section: Related Policies and Literaturementioning
confidence: 98%
“…One of our respondents commented, "It would cost you more money in the long run, if you decline to pay the bribe, so you continue to pay bribe to get things done quickly, time is money you know." According to (Abbink, Dasgupta, Gangadharan, & Jain, 2014):…”
Section: Corruption Language-evidence Gatheringmentioning
confidence: 99%